DRIVEABILITY INDEX OF COMMERCIAL GASOLINE IN ASEAN COUNTRIES - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2006)
Motor gasoline is essentialy a complex mixture of hydrocarbons distilling between about 40°C and 225°C and consisting of compounds generaly in the range C5 to C12. Small amounts of additives are also used to exchange various aspects of the performance of the fuel. Gasoline produced from different refin[1]eries can vary widely in compositions, even at the same octane level.The primary requirement of a gasoline is that should burn smoothly without exploding, under the conditions existing in the combustion chamber of the spark-ignition, so that themaximum amount of useful energy is liberated[1].The volatility of a gasoline has a vital influence on the both performance of a car emission. It affects the way car starts, the time it takes to warm up, the exten to which ice will form in the carburator, causing stalling and other problems; it influences vapour lock in the fuel system and indirectly it determines overall fuel economy. Volatility is a measure of the ability of a fuel to pass from the liquid to the vapour state under varying conditions.In cold weather, cars can take a very significant time to warm-up i.e., be capable of smooth, non-hesitating accelerations without the use of the choke. The fuel parameter that is found to have the grestest influence on warm-up is the mid-boiling range volatility as characterized by for example; the 50 per cent distillation temperature. Even after the car has warmed up, fuel volatility can still have an influence on acceleration time. Low volatility fuels obviously give leaner mixture and as mixtures leaner, acceleration performance can fall off quite rapidly.The fraction of the fuel that influences acceleration behaviour to the greatest extent is in the mid and to a lesser extent the higher boiling range. Thus, the 50% distillation temperature, sometimes together with the 90% distillation, must be controlled to ensure optimum acceleration behaviour. The factors which influence vapour lock is the volatility characteristics of the fuel. The degree to which a fuel is liable to give vapour lock depends mainly on its front end volatility. A number of different front-end volatility parameters have been used to define the vapour locking tendency of a fuel, such as RVP, percentage evaporated at 70°C, the 10 and 15% slope of the distillation curve, the vapour/liquid ratio at a given temperature and pressure. These distillation characteristics affect the following performance characteristics: starting, vapour lock and driveability.ASTM D4814-98a the standard specification for Automotive Spark-Ignition Engine Fuel has included Driveability Index as an item of performance requirement of the fuel. The inclusion of the parameter is to provide control of distillation parameters that influence cold start and warm up driveabilities.